INDONESIAN MUSLIM WEBSITES PICTURING AUSTRALIA - Budi Hapsari, Twediana (Humanities & Social Sciences Reviews, 2019)
Purpose: The relations between the neighbors Indonesia and have become interesting over the last several decades. Methodology: We have shown the important role of blended learning in the maintenance and development of the subject-subject model of interaction between students and teachers. The implementation of subject-subject interaction was considered on the example of the discipline "General and professional pedagogy", the electronic course of which is presented on the Moodle platform. Result: As the largest religious group in Indonesia, Indonesian Muslims play significant roles in shaping public opinion within society. Since the Bali Bombing 2002, there has been intense attention devoted to Australia and Indonesian Muslim issues. This paper explains how five different Indonesian Muslim websites (Arrahmah.com; hti.com; dakwatuna.com; nu.or.id & republika.co.id) portrayed Australia from 2011 to 2013. Applications: This research can be used for the universities, teachers and education students. Novelty/Originality: The ‘up and down’ tension between the ‘up and down’ tension between these countries, is influenced not only by their governments but also their citizen’s perceptions, about the other country.